Selection effects in producer-price setting - Mikael Carlsson (Sveriges Riksbank, 2014)
We use micro data on product prices linked to information on the firms that set them to test for selection effects (state dependence) in micro-level producer pricing. In contrast to using synthetic data from a canonical Menu-Cost model, we find very weak, if any, micro-level selection effects when running price change probability regressions on actual data. Also, fitting a model that nests both time- and state-dependent elements (the CalvoPlus model of Nakamura and Steinsson, 2010), the parameters mimic the standard Calvo (1983) model. Thus, upstream in the supply chain, price setting is best characterized by a very low degree of self-selection.
Keywords: D4; E3; L16; 330; Price-setting; Business Cycles; Micro Data